Animal bite cases in western Maharashtra, India: a retrospective study 2010-2015 - Vishwanath, G. R.; Rajderkar, S. S.; Sangrulkar, T. V.; Sharma, S. K.; Gajbhiye, R. I. (International Journal Of Community Medicine And Public Health, 2018)
Background: India has one of the highest numbers of cases of rabies in world. Animal bites in humans are an important public health problem. Dog bites in humans are a complex problem embracing public health and animal welfare, both in developed and developing nations. Methods: Cross-sectional record based study carried out in anti rabies clinic of Government Medical College, Miraj (1 November – 31 December, 2016). Results: Majority of victims were males and age of patient was 15-65 years, major site of bite was lower limb (58.6%). Numbers of cases were of category III bite (81.3%) and (16.4%) were of category II bite, (2.3%) cases were of category I. Conclusions: The persistence of dog bites as public health problem in Miraj and data entered into the case records of the patients was complete.